Refractive trends in Swedish Military recruits - Uhlin, Daniel; Lutteman, Sten; Jennings, J. Adrian M.; Brautaset, Rune L. (Scandinavian Journal of Optometry and Visual Science, 2011)
Purpose: The aim of the study was to determine the prevalence of refractive errors in military recruits, with special reference to myopia. Methods: 651 male military recruits, 17-23 years of age, were refracted at Pliktverket in Näsby (a National Service Administration office near Stockholm, Sweden). The refractive measurements were taken with a Topcon KR-7OOOP auto keratorefractometer during the initial health examination of National Service recruits. Results: Out of the 651 recruits the prevalence of myopia (≥- 0.50DS) was 37.7% (i.e., both eyes being myopic). The mean refractive error was RE -0.47DS and LE -0.41DS. This difference was not statistically significant. Discussion: The prevalence of myopia in Swedish military recruits has increased from 8.9% to 37.7% and the mean refractive error has changed from +0.53DS to –0.44DS since the study of Strömberg (1936). However, the prevalence of myopia in these present day recruits is lower than the 49.5% found in 12-13 year old Swedes (Villarreal et al., 2000).